Beginner Lecturer Research Protocol Typicalization of Communication Patterns of PMIK Personnel in Hospitals - Eliyah, Eliyah; Dwi Astuti, Nina; Asrining Hapsari, Meylinda (Pelopor Publikasi Akademika, 2023)
A hospital is an organization in the field of health services. In the implementation of service efforts to hospital patients, it is supported by many types of HR skills, both professional and non-professional. The provision of services is carried out by various professional groups. Professionals provide care to patients in hospitals who are routinely and certainly always in contact with patients, one of the professions in hospitals is medical recorders. The purpose of this study was to look at the picture in the environment of medical record personnel in public hospitals. The type of research used in this study is quantitative research. Quantitative research methods are one type of research whose specifications are systematic, planned and clearly structured from the beginning to the making of the research design. Organizational communication patterns are basically familiar or familial, very open, informal and full of hospitality, so it can be said that there are no secrets. Senior health workers tend to open on the left to communicate first with juniors in the workspace. Although the gap between generations still exists, seniors position themselves as older brothers to junior lecturers